HR STRATEGY IMPLEMENTATION IN A RAPID CHANGING ENVIRONMENT - Mukhlis, Suhardi; Sutardi, Sutardi; Suherry, Suherry; Sriyanti, Esi; Yeni, Afni (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to analyze the application of human resource management strategies at the Bintan Regency Environmental Office. This research is a study that uses qualitative research. The results showed that the implementation of human resource strategies at the Bintan Regency Environmental Office has been implemented but must be developed again because basically human resources have many differences for each individual. Planning at the Bintan Regency Environmental Office has been done well through planning, implementation, organizing. In terms of organizing, human resources owned by the Bintan Regency Environmental Office are still developing and training in order to implement the policies contained in the Bintan Regency regional regulations because the Bintan Regency Environmental Office is engaged in the government sector that regulates government regulations through policies that have been regulated in law.